Perceived stigma towards mental health illness and help-seeking behavior among bachelor level students: a mixed method study - Chhetri, Yamuna; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: Nepal struggles with stigma and discrimination against people with mental disorders. Mental illness is still viewed negatively by general people. The stigma is recognized as a significant public health issue and a major reason for the lower help-seeking behavior. This study aimed to find factors associated with students' perceived stigma towards mental health illness and help-seeking behavior in selected colleges of Lalitpur district using a mixed methods approach.Method: A cross-sectional study was conducted among 62 bachelor-level students from two selected colleges of Lalitpur district. Six in-depth interviews were conducted for the qualitative study. A concurrent mixed-method triangulation design was used. The Chi-square test and Braun and Clarke’s six-step thematic analysis was used to explore the factors associated with perceived mental health stigma and the help-seeking behavior of students. The results of quantitative and qualitative findings were triangulated.Result: Out of 62 participants, 53.23% participants have a high perceived stigma towards mental illness and 48.39% of the participants have good help-seeking behavior. Age, ethnicity, and faculty were significantly associated with perceived stigma. Likewise, friends or relatives with mental health issues had a significant association with help-seeking. The results of the triangulation of findings identified age and friends or relatives with mental health issues as convergent factors. Ethnicity, educational faculty, sex as divergent findings and innovative media strategies, and widespread dissemination of mental health knowledge as expansive findings.Conclusion: The factors affecting mental health stigma and help-seeking are age, ethnicity, faculty, and friends or relatives with mental health issues.